PENGARUH KONTEN MEMASAK @pattygurlz DI INSTAGRAM TERHADAP KEPUASAN FOLLOWERS - Muhammad Agil Kuncoro (2024)
There is a tendency that cooking videos require a long duration to show cooking demonstrations. Instagram @pattygurlz must show a show with a fairly short duration of 90 seconds. The reality is also that in the @pattygurlz instragram video there is no physical appearance of the presenter. This condition is a challenge to persuade Instagram users to be interested in their content without physically seeing the presenter. This study aims to determine and analyze the effect of @pattygurlz content on follower satisfaction. The research uses uses and gratification theory where audiences are considered to actively select and evaluate media that can meet their needs. This research uses a quantitative approach with a survey method. The population of this study were Instagram followers @pattygurlz with a sample size of 100. In analyzing the data, researchers conducted validity tests, reliability tests, correlation tests, regression tests, detemination coefficients, and hypothesis tests. Data testing techniques are processed using the SPSS version 26 program. The results showed a significant relationship between cooking content and followers' satisfaction. The coefficient of determination shows that 42.9% of followers' satisfaction is influenced by content, while the rest is influenced by other factors.